Fractional order electrical impedance of fruits and vegetables - Jesus, Isabel S. (2019)
The idea of fractional calculus is not new. Fractional derivatives are almost as old as integer-order definition. In 1695 Leibniz discussed this problem with L’Hospital, but many other contributions are due to investigators such as Liouville, Abel, Heaviside and Riemann, that formalized the theory of the non-integer order systems. The area of fractional calculus has primarily been the domain of mathematicians, and only had the theoretical foundation. Nowadays, this concept is employed in physics, engineering, biology, economy and other scientific fields. In our work, we apply the concepts of fractional calculus and the theory of electrical impedance to botanical elements. The fractional order behaviour of these type of systems are studied and the relation with the electrical impedance is formulated.